Motivasi Kerja Guru PAUD dan Kompetensi Pedagogik - Chairany Fadilah; Riswanti Rini; Devi Nawangsasi (FKIP UNILA, 2019)
This research is motivated by the importance of pedagogical competencies that must be mastered and applied by anearly childhood education teacher. The purpose of this research was to determine the correlation of early childhood education teacher work motivation with pedagogic competence. This research used a type ofnon-experimental quantitative research with correlational research design. The data was collected using technique of questionnaire and documentation, while technique of the sampling used was cluster random sampling. The results showed that there was very strong and significant positive correlation between of early childhood education teacher work motivation and pedagogic competence with the number 0.801. The results of work motivation data obtained from 54 respondents were 88.46% and pedagogic competence were 83.50%. Both results are in the good/high category. This means that the better/higher work motivation of a early childhood education teacherwill cause the pedagogic competence to be good/high as well. Penelitian ini dilatarbelakangi oleh pentingnya kompetensi pedagogik yang harus dikuasai oleh seorang guru PAUD. Tujuan dari penelitian ini adalah untuk mengetahui hubungan motivasi kerja guru PAUD dengan kompetensi pedagogik. Penelitian ini menggunakan jenis penelitian kuantitatif non eksperimental dengan desain penelitian korelasional. Teknik pengumpulan data menggunakan kuesioner/angket dan dokumentasi, sedangkan teknik pengambilan sampel menggunakan cluster random sampling. Hasil penelitian menunjukkan bahwa ada hubungan positif yang sangat kuat dan signifikan antara motivasi kerja guru PAUD dengan kompetensi pedagogik sebesar 0,801. Hasil data motivasi kerja yang diperoleh dari 54 responden sebesar 88,46% dan kompetensi pedagogik sebesar 83,50%. Kedua hasil tersebut masuk dalam kategori baik/tinggi. Hal ini berarti semakin baik/tinggi motivasi kerja seorang guru PAUD akan menyebabkan kompetensi pedagogiknya baik/tingi pula.Kata kunci: guru PAUD, kompetensi pedagogik, motivasi kerja